Associated production of J/ψ and D∗ in pp collisions at √ s = 13 TeV with the full Run 2 data in CMS detector and CMS-RPC upgrade project studies - Ferreira Filho, Mapse Barroso (2023)
In this work, two main subjects are addressed. The first topic concerns the Compact Muon Solenoid-Resistive Plate Chamber (CMS-RPC) upgrade project, where two main sub-topics are studied. In the first sub-topic, the performance of eco-friendly gas mixtures for the Resistive Plate Chambers (RPC) is analyzed. The performance of two gas mixtures (HFO (35%), CO2 (60%), i-C4H10 (4%), SF6 (1%) and HFO (25%), CO2 (69%), i-C4H10 (5%), SF6 (1%)) based on CO2-tetrafluoropropene is compared with the performance of the standard gas mixture (C2H2F4 (95.2%), i-C4H10 (4.5%), SF6 (0.3%)) used in the RPCs of the Compact Muon Solenoid (CMS) experiment. The performance of both ecogas mixtures is slightly lower than the performance of the standard gas mixture. Still, they can be classified as good candidates and more tests must be performed to validate the long-term operation. In the second sub-topic, the study of the aging of an iRPC prototype is discussed. The data-taking is performed at the Gamma Irradiation Facility (GIF++), a place that combines a 14 TBq 137Cs source with a high-energy particle beam. The performance results during the beam tests are satisfactory. However, during the long-term operation, the currents in one of the gaps started to increase after the accumulation of 50 mC/cm2 of charge. The cause is still being studied. In the second topic, the associated production of J/ψ and D∗ in pp collisions at √s = 13 TeV with the full Run 2 in CMS detector is analyzed. This is the first time that this measurement was performed. The cross-section has been measured in the fiducial region, 4 < p D∗ T < 60 GeV/c, |y D∗ | < 2.1, 25 < p J/ψ T < 100 GeV/c, |y J/ψ| < 1.2 as 585 ± 6 (stat) ± 52 (sys) pb, where the fraction due to the DPS contribution was estimated to be 97.5%. In this scenario, the effective cross-section was found to be 2.53+0.09−0.08 (stat) +0.25−0.29 (sys) mb.